2017
DOI: 10.3390/ma11010051
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism and Dispersion of Pseudo-Tetragonal BaTiO3-PVP Nanoparticles from Different Titanium Precursors: TiCl4 and TiO2

Abstract: Nano-sized tetragonal BaTiO3 (BT) particles that are well dispersed in solution are essential for the dielectric layer in multilayer ceramic capacitor technology. A hydrothermal process using TiCl4 and BaCl2, as source of Ti and Ba, respectively, or the precursor TiO2 as seed for the formation of BT, and poly(vinylpyrrolidone) (PVP) as a surfactant, was employed in this study to enhance both the dispersibility and tetragonality (c/a) simultaneously in a single reaction process. The process parameters, i.e., th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…18 Several parameters can also affect the shape and size of the synthesized AgNPs, such as the molecular weight, PVP concentration, and solvent. [19][20][21] PVP is stable in the keto form at acidic pH, whereas the enol tautomer exists at pH 7 and is predominant at pH > 10. 22 The keto-enol tautomerism of PVP transforms its functional group to give it different properties when it interacts with precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Several parameters can also affect the shape and size of the synthesized AgNPs, such as the molecular weight, PVP concentration, and solvent. [19][20][21] PVP is stable in the keto form at acidic pH, whereas the enol tautomer exists at pH 7 and is predominant at pH > 10. 22 The keto-enol tautomerism of PVP transforms its functional group to give it different properties when it interacts with precursors.…”
Section: Introductionmentioning
confidence: 99%
“…18 Several parameters can also affect the shape and size of the synthesized AgNPs, such as the molecular weight, PVP concentration, and solvent. 19–21…”
Section: Introductionmentioning
confidence: 99%
“…Because of the diversity of the factors that affect the synthesis of BaTiO 3 nanoparticles, hydrothermal methods are full of opportunities to improve their quality in phase composition, dimensions, and morphology. Li et al [35] reported the synthesis of tetragonal BaTiO 3 nanocrystals using TiCl 4 (or TiO 2 ) as the source of titanium, BaCl 2 as the source of barium, and polymer(vinylpyrrolidone) (PVP) as the surfactant. Grendal et al [36] used two titanium sources of amorphous titanium dioxide and a Ti-citrate complex solution to synthesize BaTiO 3 nanoparticles with a size range of 10-15 nm at different hydrothermal temperatures and times.…”
Section: Introductionmentioning
confidence: 99%